Synthesis of N,N-Dimethylaminopropyl Derivative of A Blood Sugar Antigen - Elena Di Marzo; Luigi Lay; Giuseppe D’Orazio (Molbank, 2025)
Gold nanoparticles (AuNPs) are a promising tool for drug delivery due to their unique chemical properties that make them biocompatible and easy to functionalize. However, when AuNPs are introduced into biological systems, they are coated by the so-called protein corona (PC), which affects their biodistribution and limits their therapeutic efficacy. The functionalization of AuNPs with endogenous carbohydrates can be a possible strategy to reduce immune recognition, thus enhancing their biocompatibility and circulation time. Suitable candidates for this approach are the ABO blood sugar antigens, di- and tri-saccharides that represent the terminal portion of some glycolipids and glycoproteins present on the surface of human red blood cells and other tissues. In this work, we illustrate the synthesis of trisaccharide antigen A derivative, whose last step is worthy of investigation. During the final hydrogenolysis reaction, intended to remove protecting groups, an unexpected side reaction occurred, the isolated product bearing an N,N-dimethyl moiety on the anomeric propyl linker. This side reaction might be ascribed to the in situ formation of formaldehyde and successive imine formation and reduction. The obtained compound can be used as a monomeric control compound in biochemical and structural biology studies involving ABO blood sugar antigens.